The Effect of Provision of Business Capital from the National Pension Savings Bank (BTPN) Syariah and Business Location on the Development of Small Business - Darma, Aswin Fahmi; Safaruddin Munthe; Riski Aseandi (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study aims to determine the effect of additional business capital from BTPN Syariah and business location on the development of Small Businesses in East Binjai District. This rapidly developing information technology is responded by the BTPN Syariah company, which provides business credit to mothers of underprivileged families with the aim of improving the quality of life of underprivileged mothers' families, where credit assistance is only used in order to improve their existing businesses or to open new businesses. To become a BTPN Syariah customer, the age is 18 to 25 years or married, for the beginning, but the age of 60 is also allowed, and the provision of credit without collateral. This study uses a quantitative research method, using primary data sources. The results of the study show that there is an effect of additional business capital from BTPN Syariah on the development of Small Businesses in East Binjai District. There is an effect of business location on the development of Small Businesses in East Binjai District. There is an effect of additional business capital from BTPN Syariah and business location on the development of Small Businesses in East Binjai District. Keywords: Influence of Giving; BTPN Syariah; Business Capital; Business Location; Business Development